2015
DOI: 10.1007/s10546-014-9987-2
|View full text |Cite
|
Sign up to set email alerts
|

Water-Channel Study of Flow and Turbulence Past a Two-Dimensional Array of Obstacles

Abstract: A neutral boundary layer was generated in the laboratory to analyze the mean\ud velocity field and the turbulence field within and above an array of two‐dimensional obstacles\ud simulating an urban canopy. Different geometrical configurations were considered in order to\ud investigate the main characteristics of the flow as a function of the aspect ratio (AR) of the canopy.\ud To this end, a summary of the two‐dimensional fields of the fundamental turbulence parameters is\ud given for AR ranging from 1 to 2. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Wind tunnel studies by Snyder [89] set the critical Re number at 11,000, based on the reference velocity of the free stream and building height. Later experiments either followed the aforementioned critical number [90], or directed to larger Re numbers, e.g., 19,000 [17], 37,000 [91], 44,000 [92], and 56,000 [3]. Recently Cui et al [93] reviewed the latest Re values reported in the literature and available CFD simulations with regard to the critical Re number, proposing a critical value of 32,000.…”
Section: Reynolds Numbermentioning
confidence: 99%
“…Wind tunnel studies by Snyder [89] set the critical Re number at 11,000, based on the reference velocity of the free stream and building height. Later experiments either followed the aforementioned critical number [90], or directed to larger Re numbers, e.g., 19,000 [17], 37,000 [91], 44,000 [92], and 56,000 [3]. Recently Cui et al [93] reviewed the latest Re values reported in the literature and available CFD simulations with regard to the critical Re number, proposing a critical value of 32,000.…”
Section: Reynolds Numbermentioning
confidence: 99%
“…The breeze flow is quite decreased in the urban area at roof level, but it is definitely absent at street level, since the density of the buildings and the canyon geometry (H/W > 1) determines a skimming flow regime [36], characterized by stable circulatory vortices and very weak or absent interaction with the overlying atmosphere [60][61][62]. In effect, the temperature at street level reaches its maximum between 12:00 and 16:00 LST, while at roof level it remains roughly constant.…”
Section: Summer Uhi Intensity At Microscalementioning
confidence: 99%
“…e ow rate is set by a oodgate placed at the closing section of the channel, and the water depth, h 0.16 m, is maintained constant throughout the experiments (more information about the facility can be found in [42]). e reference frame has been de ned with the x-axis aligned with the streamwise velocity and the z-axis vertical.…”
Section: The Water-channel Experimentsmentioning
confidence: 99%